Ultrasound to Localize the Peripherally Inserted Central Catheter Tip Position in Newborn Infants - Ren, Xiao-Ling; Li, Hong-Lei; Liu, Jing; Chen, Ya-Juan; Wang, Man; Qiu, Ru-Xin (American Journal of Perinatology, 2019)
Objective This study aimed to evaluate the application of ultrasound for the localization of the tip position of peripherally inserted central catheters (PICCs) in newborn infants.Study Design This study was a retrospective analysis on ultrasonic localization for PICC placement conducted in our department over the past 2 years. Ultrasonic localization was performed immediately after PICC placement in all neonatal patients. Successful PICC placement was confirmed if the PICC tip position was located at the inferior/superior cavoatrial junction. Chest X-ray localization was performed on 32 infants immediately after ultrasound examination to compare the accuracy of ultrasound localization.Results Of the 186 patients, 174 (93.5%) had successful PICC placement on the first attempt. In 11 (5.9%) patients, the catheter tip was placed beyond the ideal location as follows: too deep (in the right atrium) in 4 patients, too shallow in 4 patients, and malpositioned in 3 patients. Both the sensitivity and the specificity of ultrasound for identifying PICC tip localization were 100%. Complications occurred in 2.7% of this group of patients.Conclusion Ultrasonic localization of the PICC tip position is a timely, accurate, and reliable method and can identify the catheter tip with high accuracy. This method could be widely applied in neonatal wards.
Keywords: ultrasound; peripherally inserted central catheter; tip position; newborn infants